Oriental Houses in Baghdad: Concepts, Types, and Categories. Part III: Social Factors, Analogy with Ancient Houses, Conservation and Conclusions - al-Azzawi, Subhi
vergleicht p. 10-11 neubabylonische Wohnhäuser in Babylon und Ur.